Sistem Informasi Penjualan Pada Sandi Jati Jepara Berbasis Web - Habibullah, Riswan (Journal of Computer Science and Information System(JCoInS), 2020)
Sales is an important component in the operations of a company, so the company must be able to provide the best service to customers. In sales, it is necessary to record data about sales and inventory transactions. To help and supervise sales activities and record receipts of goods, a good information system support is needed, one technology that will provide convenience in sales, namely with computers and applications, so that it can keep abreast of companies that are growing and competing with other companies. Sandi Jati Jepara is a company engaged in the sale of clothing, each buyer must visit the store directly to carry out the purchase transaction. This results in inefficiencies in the amount of costs that are relatively small and also limited places besides that in the process of making reports and storing data it has not been well organized so as to result in a buildup or loss of sales transaction data to overcome the problem, then we need a modern system that is very suitable to support the progress and development of the company, so that it can overcome problems or constraints on the system that is running. In this case, to maximize the existing system, the design uses the language Unified Modeling Language (UML) and is implemented using PHP, Xampp, Web Server and MySQL Server.